Development of a novel image-based program to teach narrow-band imaging. (August 2016) - Dumas, Cedric; Fielding, David; Coles, Timothy; Good, Norm
Objectives: Narrow-band imaging (NBI) is a widely available endoscopic imaging technology; however, uptake of the technique could be improved. Teaching new imaging techniques and assessing trainees' performance can be a challenging exercise during a 1-day workshop. To support NBI training, we developed an online training tool (Medimq) to help experts train novices in NBI bronchoscopy that could assess trainees' performance and provide feedback before the close of the 1-day course. The present study determines whether trainees' capacity to identify relevant pathology increases with the proposed interactive testing method. Methods: Two groups of 20 and 18 bronchoscopists have attended an NBI course where they did a pretest and post-test before and after the main lecture, and a follow-up test 4 weeks later to measure retention of knowledge. We measured their ability to mark normal and abnormal 'biopsy size' areas on bronchoscopic NBI images for biopsy. These markings were compared with areas marked by experts on the same images. Results: The first group results were used to pilot the test. After modifications, the results of the improved test for group 2 showed trainees improved by 32% (total class average normalized gain) in detecting normal or abnormal areas. On follow-up testing, Group 2 improved by 23%. Conclusions: The overall class average normalized gain of 32% shows our test can be used to improve trainees' competency in analyzing NBI Images. The testing method (and tool) can be used to measure the follow up 4 weeks later. Better follow-up test results would be expected with more frequent practice by trainees after the course.